Socio-demographic determinants of paediatric tuberculosis patients in an urban city of Central India - Joshi, Sheloj; Saxena, Dineshkumar M.; Joshi, Mahesh Kumar (International Journal Of Community Medicine And Public Health, 2017)
Background: Paediatric tuberculosis (TB) indicates presence in the community of sputum -positive pulmonary tuberculosis, presence of childhood risk factors for disease and stage of epidemic. This "orphan disease" exists in the shadow of adult TB and is a significant child health problem, but is neglected. As a result both research and surveillance data in the field of childhood TB has been greatly limited. Objective of the study was to find out the socio-demographic profile of paediatric TB patients registered under RNTCP in Bhopal city. Methods: A study was conducted in all tuberculosis treatment units (TU) of Bhopal city. All paediatric patients in the age group of 0 to 14 years diagnosed as TB and registered under RNTCP and fulfilling inclusion criteria during January to June 2013 (six months) were included in the study. The data was analysed on statistical software SPSS VS.20. Results: The maximum numbers of patients (66.06%) were in the age group of 1-10 years. More than half of the mothers and fathers of paediatric patients are either illiterate or having low educational status. In our study 92.72% of patients belonged to low socio economic status and also 69.09% of paediatric patients lived in overcrowded households and were malnourished. Conclusions: The study concluded that tuberculosis in children affects mainly the age group of 1-10 years and is more common in females. Poor housing conditions contribute to tuberculosis incidence as majority of the paediatric patients lives in semi Pucca and Kaccha house and gave a history of dwelling in overcrowded houses. Majority of children were malnourished.